2016
DOI: 10.1111/mec.13893
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term dynamics in microbial eukaryotes communities: a palaeolimnological view based on sedimentary DNA

Abstract: Assessing the extent to which changes in lacustrine biodiversity are affected by anthropogenic or climatic forces requires extensive palaeolimnological data. We used high-throughput sequencing to generate time-series data encompassing over 2200 years of microbial eukaryotes (protists and Fungi) diversity changes from the sedimentary DNA record of two lakes (Lake Bourget in French Alps and Lake Igaliku in Greenland). From 176 samples, we sequenced a large diversity of microbial eukaryotes, with a total 16 386 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 106 publications
(231 reference statements)
2
75
1
Order By: Relevance
“…A relatively high richness in the MECs from Lake Bourget was revealed over the last 100 years (6,515 OTUs) in comparison with the richness detected for the last 2,100 years in the same lake applying the same methodology (11,344 OTUs; Capo et al ., ). Studies investigating lacustrine MEC diversity generally differ in their experimental procedures (choice of barcodes, depth of sequencing and the stringency of bioinformatics treatments).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A relatively high richness in the MECs from Lake Bourget was revealed over the last 100 years (6,515 OTUs) in comparison with the richness detected for the last 2,100 years in the same lake applying the same methodology (11,344 OTUs; Capo et al ., ). Studies investigating lacustrine MEC diversity generally differ in their experimental procedures (choice of barcodes, depth of sequencing and the stringency of bioinformatics treatments).…”
Section: Discussionmentioning
confidence: 97%
“…The low proportion and richness found here for Amoebozoa, Exacavata are classical in lakes MECs (e.g., Nolte et al ., , Mangot et al ., , Simon et al ., ; Capo et al ., ; Filker et al ., ). However, our stringent methodological procedure has certainly accentuated this pattern, in particular due to the choice we made to remove of all OTUs which were not detected in the two replicates done for each sample; for instance, Parabasalia (Excavata) and Euglenozoa (Excavata) were recorded in the molecular inventories before this filtering.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, fungal community composition in the sediment of two European lakes was related to the past two millennia of paleoclimatic variations (Capo et al, 2016). The relationship between late Quaternary climate change and soil fungal community composition may be caused by altering the relative abundance of fungi (Capo et al, 2016), as reported in previous studies that regions where the late Quaternary climate oscillations were similar tend to promote assemblages with similar certain community compositions (Svenning et al, 2015).…”
Section: Discussionmentioning
confidence: 52%
“…While there is a paucity of studies to compare this to, it has been shown that fungal richness in the sediment of two European lakes was not related to the past two millennia of paleoclimatic variations (Capo et al, 2016). While there is a paucity of studies to compare this to, it has been shown that fungal richness in the sediment of two European lakes was not related to the past two millennia of paleoclimatic variations (Capo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%